Service Quality And Product Quality In Influence Ud Karomah Abadi Makmur Customer Loyalty - Ramadhan Chossy Pratama; Dyan Arintowati; Muhammad Bawono; Rendi Dwi Apriansa (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2023)
The aim of this research is to prove the influence produced by product quality and service quality in maintaining the loyalty of a company's consumers partially or simultaneously. This is intended to find out to what extent service quality and product quality can protect a company from its competitors.The research method used is a correlational quantitative method sourced from data obtained from questionnaire results. Questionnaires that have been filled out by respondents will be grouped and the results analyzed using the SPSS application. The results obtained from this study are that service quality with tcount ≤ ttable, namely -1.399 ≤ 1.99834 and a significance level of ≤ 0.05, namely 0.167 ≥ 0.05, means that it partially has no positive and significant effect on consumer loyalty, which means that If service quality increases, consumer loyalty will not increase.Meanwhile, partially product quality with a calculated t value ≥ t table, namely 7.350 ≥ 1.99834 and a significance level ≤ 0.05, namely 0.000 ≤ 0.05, has a positive and significant influence on consumer loyalty, so that if product quality increases, consumer loyalty has also increased. Even though the results are partially different, simultaneously service quality and product quality have a positive and significant influence on consumer loyalty with proof that the SPSS calculation results are Fcount ≥ Ftable (33.047 ≥ 2.751) and the significance level is (0.000 ≤ 0.05).